Particle filtering based semi-blind estimation for MIMO-OFDM time-varying channel - JING Yuan; YIN Fu-liang; ZENG Shuo (Tongxin xuebao)
A semi-blind channel estimation method based on the particle filtering was proposed for the MIMO-OFDM wireless communication system.By optimizing the particles distribution locally,the traditional particle filtering algorithm was modified,and a local optimized particle filtering was proposed.This local optimized particle filtering can achieve the low MSE,and improve the precision of the MIMO-OFDM time-varying channel estimation.Since this method was per-formed in frequency domain,it was not necessary to know（or estimate） the length of the channel.Compared with exist-ing approaches,the proposed method was more robust to the non-gauss distribution noise and the detection performance is nearly optimal.The simulation results show the effectiveness of the proposed method.